Environmental sustainability for selected packaging wastes - Korkmaz, Asude Pelin. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2019., 2019)
Rapid production and consumption have led to increase in the waste generation in the past several decades. According to the Eurostat (2018) 19% of total municipal solid waste is comprised of packaging waste. To alleviate the environmental impacts associated with packaging waste in both production and disposal phases, recycling is a key solution. The aim of this study is to evaluate selected plastic and glass beverage packaging wastes in Turkey according to the national recycling targets using a Life Cycle Assessment (LCA) methodology and provide science-based recommendations for development of roadmap for achieving sustainable consumption and production goals. For this purpose, the current years (2017 and 2018) and the future (2025) national and EU recycling targets were assessed by LCA on an annual basis. The data for both production and recycling processes were obtained from packaging factories and recycling facilities. The energy processes used in the study were calculated according to the primary energy sources of the relevant year. With this study, the contribution of recycling to the environmental impacts of glass and PET packaging during the life cycle was analyzed.
Keywords: Packaging waste.; Recycling (Waste, etc.); Environmental responsibility.